2019
DOI: 10.3389/fimmu.2019.00031
|View full text |Cite
|
Sign up to set email alerts
|

p31-43 Gliadin Peptide Forms Oligomers and Induces NLRP3 Inflammasome/Caspase 1- Dependent Mucosal Damage in Small Intestine

Abstract: Celiac disease (CD) is a chronic enteropathy elicited by a Th1 response to gluten peptides in the small intestine of genetically susceptible individuals. However, it remains unclear what drives the induction of inflammatory responses of this kind against harmless antigens in food. In a recent work, we have shown that the p31-43 peptide (p31-43) from α-gliadin can induce an innate immune response in the intestine and that this may initiate pathological adaptive immunity. The receptors and mechanisms responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 37 publications
3
53
0
1
Order By: Relevance
“…In a previous report, we showed by TEM that p31‐43 self‐aggregates presenting a PPII structure, in agreement with CD determinations . Subsequent NMR experiments performed by Calvanese et al confirmed that this peptide is able to adopt this structure.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…In a previous report, we showed by TEM that p31‐43 self‐aggregates presenting a PPII structure, in agreement with CD determinations . Subsequent NMR experiments performed by Calvanese et al confirmed that this peptide is able to adopt this structure.…”
Section: Resultssupporting
confidence: 86%
“…We observed that wild‐type mice treated with p31‐43 presented histological alterations and increased number of intraepithelial lymphocytes, production of proinflammatory mediators and cell death. We also demonstrated that biological effects depend on the activation of the NLRP3 inflammasome . In the other hand, Villella et al .…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations